Yeast vitality determination based on intracellular NAD(P)H fluorescence measurement during aerobic-anaerobic transition - Kurec, M; Kuncová, G; Brányik, T (Folia microbiologica, 2009)
This work presents a yeast-cell vitality-assessment method based on on-line intracellular fluorescence measurement. The intracellular NAD(P)H fluorescence of a cell suspension is recorded during transition from aerobic to anaerobic conditions and the output signal is evaluated as a measure of yeast vitality (quality). This fluorescence method showed a highly satisfactory correlation with even low dead cell numbers where the acidification power test could not be applied.
Keywords: Saccharomyces cerevisiae; Spectrometry, Fluorescence; NADP; mikrobiální viabilita; anaerobióza; aerobióza; fluorescenční spektrometrie; Aerobiosis; NAD; Anaerobiosis; Microbial Viability